2000
DOI: 10.1086/317194
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Classic FR II Broad Absorption Line Quasar from the FIRST Survey

Abstract: We have discovered a remarkable quasar, FIRST J101614.3]520916, whose optical spectrum shows unambiguous broad absorption features, while its double-lobed radio morphology and luminosity clearly indicate a classic Fanaro †-Riley type II radio source. Its radio luminosity places it at the extreme of the recently established class of radio-loud broad absorption line quasars. Because of its hybrid nature we speculate that FIRST J101614.3]520916 is a typical FR II quasar that has been rejuvenated as a broad absorp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 42 publications
9
76
1
1
Order By: Relevance
“…Gregg et al (2000) suggest that this quasar rather happens to be seen in a rare and short-lived state, showing both, BAL features and developed radio lobes at the same time, and postulate that it is a rejuvenated quasar, possibly through merger. Contrary to this conclusion we claim that these observations actually support the orientation model.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Gregg et al (2000) suggest that this quasar rather happens to be seen in a rare and short-lived state, showing both, BAL features and developed radio lobes at the same time, and postulate that it is a rejuvenated quasar, possibly through merger. Contrary to this conclusion we claim that these observations actually support the orientation model.…”
mentioning
confidence: 86%
“…In the special case of the quasar FIRST J101614.3+520916 Gregg et al (2000) find BAL features in the optical and radio loud emission from lobes of classic FR II type at the same time. According to the authors this quasar has some properties in common with low-ionization BAL QSOs, as for example higher reddening.…”
mentioning
confidence: 91%
“…The last column shows the notes on individual sources, i.e., details about the calculation of the BI or the reference from which we gathered information about the object. (6): X-ray analysis used in this work: a − spectral analysis, HR − hardness ratio analysis; Col. (7): number of individual XMM-Newton observations; Col. (8): notes on individual objects: "Mg II" denotes LoBAL, which BALnicity index were computed from Mg II absorption troughs; "Cr" -the optical spectrum was retrieved from Croom et al (2004); "C" -optical spectra courtesly provided by Cocchia et al (2007); "Br" -optical spectra from AXIS survey courtesly provided by Barcons et al (2002); "W" -BALnicity index value was taken from Weymann et al (1991); "H" -reconstructed spectrum from Hines & Wills (1995); "St" -reconstructed spectrum from Stern et al (2002); "P" -optical spectra courtesly provided by Prescott et al (2006); "Wi" -BALnicity index value was taken from Wills et al (1999); "Gr" -BALnicity index value was taken from Gregg et al (2000); "G" -BALnicity index value was taken from Goodrich et al (2001); "LH" -spectra were taken and reconstructed from Lehmann et al (2001); "Hu" -BALnicity index value was taken from Hutsemékers & Lamy (2000); "F" -reconstructed spectrum from Foltz et al (1987); "J" -reconstructed spectrum from Junkkarinen et al (1987); "Mor" -reconstructed spectrum from Morris et al (1991). The spectra for rest of the objects were retrieved from the SDSS archive and correspond to the following catalogues: Trump et al (2006); Shen et al (2008) and Gibson et al (2009).…”
Section: The Samplementioning
confidence: 99%
“…In general, the radio-loud BALQs tend to be compact in the radio, similar to gigahertz-peaked spectrum (GPS) and compact steep spectrum (CSS) sources, which are thought to the progenitors of large-scale radio sources Montenegro-Montes et al 2009). It has been proposed that the BALs are not closely related with the inclinations, and may be associated with a relatively short-lived evolutionary phase with a large BAL-wind covering-fraction (e.g., Briggs et al 1984;Gregg et al 2000). We found that the two radio-loud steep spectrum BALQs in this current paper have different radio structures.…”
Section: Balqsmentioning
confidence: 48%